2019
DOI: 10.1021/acs.nanolett.9b01703
|View full text |Cite
|
Sign up to set email alerts
|

Regaining a Spatial Dimension: Mechanically Transferrable Two-Dimensional InAs Nanofins Grown by Selective Area Epitaxy

Abstract: We report a method for growing rectangular InAs nanofins with deterministic length, width and height by dielectric-templated selective-area epitaxy. These freestanding nanofins can be transferred to lay flat on a separate substrate for device fabrication. A key goal was to regain a spatial dimension for device design compared to nanowires, whilst retaining the benefits of bottom-up epitaxial growth. The transferred nanofins were made into devices featuring multiple contacts for Hall effect and fourterminal res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 96 publications
4
45
0
Order By: Relevance
“…16,23–25,29–32 The small interface area helps to limit the formation of interface related defects, and the shape of the nanostructure can be controlled by the geometry of the openings. 16,29,33,34 While this helps minimise the interface related defects, there are other sources of defects in Zn 3 P 2 . 35–38 Various defect levels in the bandgap have been experimentally probed by various groups previously, but very few have been able to describe the exact origins.…”
Section: Introductionmentioning
confidence: 99%
“…16,23–25,29–32 The small interface area helps to limit the formation of interface related defects, and the shape of the nanostructure can be controlled by the geometry of the openings. 16,29,33,34 While this helps minimise the interface related defects, there are other sources of defects in Zn 3 P 2 . 35–38 Various defect levels in the bandgap have been experimentally probed by various groups previously, but very few have been able to describe the exact origins.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Sasa Gazibegovic et al grew InSb nanosheets directly from a InSb substrate platform without any foreign stem formation [ 64 ]. With a SiO x dielectric template fabricated by a mask transfer process by the plasma-enhanced CVD, the rectangular InAs nanofins with definite length, width and height can be synthesized at the rectangular opening using the MOCVD method ( Figure 5 c) [ 63 ]. By controlling the In flux, the morphology of InAs can be adjusted from 1D NWs to 2D nanosheets ( Figure 5 d) [ 28 ].…”
Section: Growth Of Iii–v Nanostructures: Synthesis and Structurementioning
confidence: 99%
“…[8] These drawbacks motivate the exploration of 2D and 3D nanostructures with sophisticated shapes and more functionalities. [9][10][11][12][13][14][15][16][17][18][19][20] For instance, Chi et al [21] reported twin-free GaAs nanosheets which have the advantage of membranelike geometry over nanowires in realizing crystal perfection. 2D and 3D nanostructures also present superior material performance, such as enhanced light scattering and second harmonic generation in V-shaped InAs nanomembranes, [22,23] large-scale emission homogeneity of InP nanorings, InP and GaAs nanomembrane arrays, [4,24] outstanding quantum transport and electronic properties of InSb nanosheets, [25][26][27][28] and reduced piezoelectric field inside InGaN quantum wells grown on nonpolar sidewalls of GaN nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…[19,29] Furthermore, the larger dimensions also make device fabrication easier. [10,27,28] More recently, complex III-V networks grown by SAE technique are extensively investigated because of their great potential in quantum science. [20,[30][31][32][33][34] All these works show the significance of shape engineering in fundamental research and device applications from diverse perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation